Aumento do acesso à Internet em banda larga no Brasil e sua possível relaç\~ao com o crescimento econômico: Uma análise de dados em painel - Hildebrando Rodrigues Macedo; Alexandre Xavier Ywata de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– Applying econometric models on panel data, we analyzed the possible relation between the increase in broadband Internet access density in Brazil and the GDP and GDP per capita growth. Broadband access densities, GDP, GDP per capita and the population education level data were disaggregated at State level. Data regarding investment in telecommunications we used at the country level. Data for broadband access density per State, between 2000 and 2006, had to be estimated based on the data available at the country level, because data detailed at State (and municipality) levels are available only for 2007 and onwards.
Keywords: C21; O33; 330; Internet; Nationaleinkommen; Bildungsniveau; Brasilien